Comprehensive Analysis on Prognosis and Immune Infiltration of Lysyl Oxidase Family Members in Pancreatic Adenocarcinoma With Experimental Verification - Jiang, Chao; Wang, Meng; Yao, Weikai; Lv, Guoyue; Liu, Xueyan; Wang, Guangyi (Frontiers in Molecular Biosciences, 2022)
Background: Pancreatic adenocarcinoma (PDAC) is the most aggressive among all solid malignancies with delayed disease detection and limited effective treatment. However, due to the intricate heterogeneity and exclusive tumor microenvironment (TME), the development of effective therapy has been facing enormous challenges. The lysyl oxidases (LOXs) underpin the shaping of the TME to promote cancer growth, metastasis and modulate response to treatment. Materials and Methods: The mRNA expression, prognostic, and clinicopathological data for LOXs in PDAC from multiple open-access databases were summarized and analyzed. The protein expression was verified by immunohistochemistry (IHC). Co‐expressed genes of LOXs were predicted and elaborated by LinkedOmics. Functional enrichment analysis of LOXs co‐expressed genes was performed using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG). TIMER and TISIDB were applied to analyze the relationship between LOXs expression and immune infiltration. Results: The mRNA expression levels of LOX, LOXL1 and LOXL2 were significantly higher in PDAC, the expression levels of LOXL3 and LOXL4 were contrary in different databases. High mRNA levels of LOX and LOXL2 were associated with advanced PDAC stage, while elevated LOX and LOXL3 expression correlated with high tumor grade. The IHC staining showed higher expression levels of LOX, LOXL1 and LOXL2, lower expression of LOXL3 in PDAC tissues, while the protein expression of 4 made no difference. For all LOXs co-expressed genes and the overlapping co-expressed genes of each LOX member, functional enrichment analysis showed a close relationship with extracellular matrix (ECM) regulation, except that LOXL3 and its ligands were highly associated with immune-related functions. Further analysis suggested that LOX and LOXL3 expression strongly correlated with tumor-infiltrating lymphocytes (TILs), various immune signatures, and immune checkpoints. Finally, survival analysis revealed high LOX and LOXL2 expression predicted worse overall survival (OS), progression-free interval (PFI), and disease-specific survival (DSS). Conclusion: These findings indicated that the LOX family, especially LOX and LOXL2, might have a prospective value in PDAC oncogenesis, and they may become prognostic biomarkers, revealing a promising field in targeted therapy.